Effect of Managers’ Illusion of Control and Corporate Governance Structure on the Sensitivity of Investment Cash Flow - Hsu, Ai-Chi; Chen, Hsu-Sheng (International Journal of Economics and Financial Issues, 2017)
This study examines publicly listed Taiwanese companies to explore the effect of managers’ illusion of control on the sensitivity of investment cash flow, as well as the adjustment effects of different corporate governance structures. We constructed various proxy variables and found that non-operating income and expense has a significant positive impact on future capital expenditure ratios. As the company’s operating risk increases, managers are more willing to invest, showing managers’ confidence in their own expertise and their optimistic expectation to control future scenarios. The results related to corporate governance structures showed that co-governance and expert management governance mechanisms tend to mitigate managers’ illusion of control, weakening the investment cash flow sensitivity. Government control models did not show a significant impact and there was no significant adjustment effect on the investment cash flow sensitivity. Firms with single-family governance may have agency problems and strengthen the investment cash flow sensitivity. Keywords: illusion of control, non-operating income and expense, investment cash flow sensitivity JEL Classifications: G30, G31